(untitled) (Herald of Journalism, 2025)
Despite the surge of interest in digitalization across the globe, comprehensive research on the post-pandemic digital trajectories of Central Asian countries remains limited. Particularly, Kazakhstan and Uzbekistan, the leading economies of the region, exemplify digital transformation in emerging markets, under different challenges and opportunities. Thus, to fill this gap, the current research tracks the digitalization trends in Kazakhstan and Uzbekistan in the post-pandemic world. The study aims to analyze and compare local and international digitalization indicators of the countries, focusing on ICT development, digital media markets (particularly video streaming and investment in digital marketing), internet penetration rate, median speed of the internet, social media statistics, messaging platforms, mobile connectivity, and overall digitalization trends. The relevance of this study stems from its focus on examining how digitalization affects the process of integration of these countries into the global digital economy. The research method employs quantitative and content analyses descriptive of the digital landscapes of Kazakhstan and Uzbekistan, thus delivering a meaningful mix of numerical data and contextual insight about their digital transformations. The results of the study give an indicative manifestation of both the attainments and challenges in the digital transformation of these two countries. Findings demonstrate the impact that ICT can have on determining the digital paths of Kazakhstan and Uzbekistan. Offering insights into evolving digitalization dynamics in Central Asia, this research contributes to the growing body of academic discourse and serves as a resource for decision-makers, businesses, and researchers tracking the region’s digital transformation and its wider ramifications.